Implementation of Public Sector Accounting in Indonesia - Hamzah, Hajrah; Kusumawati, Andi; Nirwana, Nirwana (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
The purpose of this research is to be able to describe broadly the development of public sector accounting research in Indonesia. Charting the field is the research methodology used. 40 articles related to public sector accounting from 11 Indonesian journal publications with accreditation were collected between 2013 and 2022 as samples. Topics and methods are assessed as categories that are classified in this study. According to the results of the research analysis, financial accounting is an issue that is often applied, namely public sector accounting, and a quantitative approach together with survey and descriptive methods is the most widely used modeling technique. The topic usually observed is financial accounting in the public sector because there are some governments that are constrained by reporting their finances and because accounting in the public sector continues to be a unique issue. Meanwhile, the regulation topic category is one of the less researched topics of the five topic categories in this study.